Comparison of Class A pan evaporation with estimated reference evaporation and evapotranspiration - Simon-Gáspár, Brigitta; Soós, Gábor; Anda, Angéla (GEORGIKON FOR AGRICULTURE, 2022)
Aquatic plants (macrophytes) can have a large effect on water evaporation, yet they are ignored when determining evaporation from lakes and reservoirs. The aim of the experiment was to determine the effect of a floating leaf macrophyte (Nuphar lutea, yellow water lily) on evaporation. The measured evaporation data were also compared with the calculated from the evaporation/evapotranspiration formulas used in the literature (Shuttleworth, FAO56 Penman-Monteith, Hargreaves-Samani and Priestley-Taylor formula). The results showed that the presence of yellow water lily increase Class A pan evaporation. Of the empirical formulas, the FAO-56 Penman-Monteith reference evapotranspiration values were closest to the observed evaporation values.
Keywords: evaporation; class A pan; floating leaf macrophyte